PHYSICO-CHEMICAL CHARACTERISTICS OF TRIBAL BEAN (Canavalia virosa) AND ITS ALTERNATIVE TOFU AND TEMPEH FOOD PRODUCTS - Djaafar, Titiek F.; Cahyaningrum, Nurdeana; Purwaningsih, Heni (Indonesian Journal of Agricultural Science, 2010)
Increasing price of soybean becomes a serious problem for producers of traditional foods such as tempeh and tofu. These traditional foods are important protein sources for many Indonesian people. Tribal bean (Canavalia virosa) could be used as a substitution of soybean for tempeh and tofu processing. This study aimed to determine physico-chemical characteristics of tribal bean and its products such as tofu and tempeh. Tribal bean old pods were peeled manually in the Postharvest and Agricultural Machinery Laboratory of the Yogyakarta AIAT. The peeled seeds were dried until 10% water content and their epidermis were removed mechanically by using an abrasive peeler to produce yellowish clean peeled beans. The beans were analyzed physically and chemically using the standard prosedure. Since the tribal bean seeds contained high HCN, to minimize HCN content the beans were presoaked for 48 hours in water. The beans were then mixed with soybean at a ratio of 50:50 or 25:75 and processed for making tempeh and tofu using traditional method. Physicochemical and organoleptic characteristics of the tribal bean tempe and tofu were analysed, involving organoleptic test with hedonic method, texture, as well as water, ash, protein and crude fiber contents. The results showed that tribal bean contained protein (37.30%), essential amino acids, minerals and fiber (3.1%), and a toxic substance HCN. Presoaking the beans in water for 48 hours significantly reduced HCN content by 98.51%, from 1334 ppm. Tofu made of a mixture of tribal bean and soybean at a ratio of 25:75 plus 2% rice vinegar as a coagulant has a white color and normal flavor appearances, and was accepted by panelists. The tribal bean tempeh contained 78.1% water, 1.21% ash, 8.14% protein, 3.1% crude fiber, and 44 ppm HCN. Tempeh made of a mixture of tribal bean and soybean at ratios of 50:50 and 25:75 showed good characters (flavor, taste, color, and texture) and panelist acceptance, as well as nutrition values (76% water, 2.71% ash, 14% protein, 0.25% crude fiber, and 14% lipid). However, HCN content in the tofu was still higher (85 ppm HCN) than the recommended maximum value of 50 ppm. This study suggests that tribal bean is more suitable for tempeh than for tofu based on its HCN content.